Skargi wyborcze do Sądu Najwyższego w sprawie wyników wyborów prezydenckich w Kenii. Krótka historia ze szczególnym uwzględnieniem wyroku Sądu Najwyższego z 2017 roku - Ochieng’, Maryanne Awiti (Studia Wyborcze, 2020)
This article focuses on Kenya’s political system from independence to date; the conduct of elections under different regimes; and the clamour for multi-party democracy in the 1990s. It then delves briefly into the 2007 general elections, in particular the presidential election that was highly competitive, the contested 2007 presidential election results that left many people dead or displaced. Consequently, it explores the state’s efforts for electoral reforms that culminated in the promulgation of the new constitution in 2010. The article also discusses presidential petitions but with a major focus on the 2017 presidential petition. This is mainly because, in a clear demonstration of judicial independence, the Supreme Court nullified the presidential election results on the basis that the election was not conducted in compliance with the principles set out in the Constitution and election laws, and that the presidential election was marred by irregularities.